Marxism and urban culture - Fraser, Benjamin; Roberts, Les, 1966-; Compitello, Malcolm Alan, 1946-; Léger, Marc James, 1968-; Sorochan, Cayley; Vrana, Heather A.; Hicks, Jeff; DeFazio, Kimberley; Versieren, Jelle; De Smet, Brecht; Yang, Manuel; Haraguchi, Takeshi; et al. (Lexington Books, 2014)
Marxism and Urban Culture takes a broad view of Marx's legacy and-largely in the spirit of Marxist urban geographers Henri Lefebvre and David Harvey-applies that legacy to cultural practices and products from across the globe. Cities explored include Bologna, Buenos Aires, Guatemala City, Liverpool, London, Los Angeles, Madrid, Mahalla al-Kubra, Mexico City, Montreal, Osaka, Strasbourg, and Vienna.